An investigation into the popularity of the Zimbabwean tabloid newspaper, uMthunywa: a reception study of Bulawayo readers - Mabweazara, Hayes Mawindi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
The development of the tabloid press has stirred heated debate among media scholars. Critics have argued against the relevance of tabloids in society, often framing them as the 'journalistic other' deserving no place in 'serious' journalism. Much of this criticism, however, has not been based on a close interrogation of the phenomenon, or an examination of the reasons for their popularity amongst readers. It is against this background that this study investigates the reasons behind the popularity of the Zimbabwean state-controlled tabloid newspaper uMthunywa, among its Bulawayo readers. In particular, it explores the meanings obtained from the content of the paper and the relevance of this content to the readers' everyday lives. In undertaking this investigation, the study draws primarily on qualitative research methods, particularly qualitative content analysis and in-depth interviews (both group and individual). As the study demonstrates, these methods uncover the complex manner in which Bulawayo readers are attracted to uMthunywa and how they appropriate its textual meanings to their lived realities. The study establishes that despite uMthunywa being state-controlled, it offers space through which the conventional ways of presenting reality are challenged, and the importance of the newspaper being written in isiNdebele. As the study indicates, the popularity of the newspaper is largely dependent on its excessive formulaic and sensational stories, which cover issues experienced by its readers in their lived circumstances. The study thus argues that the newspaper constitutes an alternative mediated public sphere that finds space in the deeper social conditions that have alienated the people of Bulawayo from the macropolitical life of the nation and the 'power bloc'.
Keywords: uMthunywa (Zimbabwe); Tabloid newspapers -- Zimbabwe; Journalism -- Zimbabwe; Newspapers -- Marketing -- Zimbabwe; Mass media -- Social aspects -- Zimbabwe